The Impact of Zakat on the Economy and Poverty in Indonesia - Sri Runtiningsih; Risanda Alirastra Budiantoro; Ahmad Syahrul Fauzi; Ubaedul Mustofa; Lailatis Syarifah; Dwi Rahmayani (Journal of Islamic Economic Laws, 2026)
This study aims to examine the impact of zakat and various socio-economic factors on regional economic growth and poverty levels in Indonesia. Using panel data from 34 provinces in Indonesia for the period 2019-2021. This study examines the complex relationships between zakat distribution and key macroeconomic indicators within an Islamic economic framework, using a common effects model for the economic growth equation and a fixed effects model for the poverty equation. The results indicate that zakat has a positive significant effect on economic growth and has a negative  significant effect on poverty. This research provides valuable insights into the potential role of zakat in addressing economic inequality and promoting sustainable development in Indonesia.